(untitled) (Iranian Journal of Kidney Diseases, 2016)
Treatment of retroperitoneal fibrosis usually involves corticosteroids with or without other immunomodulating medications or tamoxifen. Rituximab, a monoclonal antibody that specifically targets CD20 on the surface of B-cells, is effective in achieving complete remission of proteinuria in patients with idiopathic membranous nephropathy. We describe a case of a 45 years old man with idiopathic membranous glomerulonephritis (with proteinuria of more than 30 grams/24 hours) and simultaneously with idiopathic retroperitoneal fibrosis (with large number of cells CD20 in the histologic image). The patient did not tolerate the treatment by cyclophosphamide, and as rescue therapy, administration of rituximab was indicated with excellent effect. We recorded promptreduction of proteinuria and significant reduction of retroperitoneal fibrosis. Rituximab is effective in treatment of idiopathic retroperitonea lfibrosis with positivity of CD20 cells, as well as in treatment of idiopathic membranous glomerulonephritis.